COME AND WITNESS ANOTHER EXCITING EDITION OF PESTA HOKI USM-PENANG INTERNATIONAL AT USM STADIUM - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 23 November 2016 The 43rd Pesta Hoki USMPenang International will begin this Friday, 25 November till 27 November at USM Minden Field and Hockey Stadium.